Teaching english rhythm to first-year english-majors at Ton Duc Thang university: problems and suggestions - Do , Anh Thu (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
Rhythm is of great importance during teaching English in general and pronunciation in particular. However, due to the particular characteristics of rhythm, together with a couple of affecting factors, teaching English rhythm was supposed to be faced with a number of hypothetical problems which were considered as the conceptual framework of the study. The study found out that most of students had (i) no interest and motivation in learning English rhythm, (ii) no background knowledge of English rhythm, (iii) no adequate opportunities to practice English rhythm outside class, (iv) negative psychological symptoms when practicing English rhythm, (v) spoken English with Vietnamese rhythm; and (vi) teaching and learning English rhythm had no or low priority, not enough teaching time and materials.